EFFECT OF CULTURAL MEDIA AND NUTRIENT SOLUTION ON QUALITY AND PRODUCTION OF CUCUMBER BY USING HYDROPONIC SYSTEM - & Hassan, Obaid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study to improve the growth, production, and fruits quality of cucumber, Two experiments were carried out. firstly; a field experiment to produce cucumber by the soilless culture system. This experiment was to study effect of nutrients solution (A1, A2), growth media (C1, C2, C3, and C4), and methods of flowering management (B1, B2, B3 and B4). Second experiment was conducted to study the effect of storage methods on the yield of 32 field treatments combination (ABC), for a week in four cases of storage as follows: S1 represented the storage by using perforated polyethylene bags at 25°C, while S2 at 7°C. S3 storage by using non-perforated bags at 25°C, and S4 represented the storage by using non-perforated bags at 7°C. The results were revealed that the plant nutrition by using standard solution (A1) had significantly superior in percentage calcium in the leaves (%3.4), firmness (9.27kg.cm2), and TSS% (%5.81) of fresh fruits. Commercial solution (A2) results indicated significantly superior in number of the fruits (54.24 fruit.plant-1) and plastic house production (9.46 tons). The highest yield was 10.84 ton.house-1 produced at the A2B2C1 field treatment combination. The best quality (TSS%) was 5.51% in the case of a storage S2 and the lowest fruits weight loss was 1.90% in the case of S4.